2017
DOI: 10.9734/ajaar/2017/34875
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Current Status of Agricultural Extension Service in Nigeria

Abstract: This study reviewed on the current status of agricultural extension in Nigeria. Numerous extension approaches have been used in Nigeria. The basic and essential task of agricultural extension has been and still is: The exchange and means of sharing information, knowledge and skills for improved livelihood regardless of its organization. In a changing world and its environment, however, the context and hence the challenges in agricultural extension service changes; such as: improvement in agricultural productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Its weaknesses had been its top-down nature, unbending, and non-sustainable (Chambers et al, 2013). However, it has been used by several government extension programs in third-world nations such as Nigeria (Hamisu et al, 2017).…”
Section: Training and Visits (T And V)mentioning
confidence: 99%
“…Its weaknesses had been its top-down nature, unbending, and non-sustainable (Chambers et al, 2013). However, it has been used by several government extension programs in third-world nations such as Nigeria (Hamisu et al, 2017).…”
Section: Training and Visits (T And V)mentioning
confidence: 99%
“…Issues relating to agricultural extension policy are likely to have a significant impact on the achievement of adequate agricultural productivity and food and nutrition security in Nigeria. A review of recent studies (Omotayo, Chikwendu, and Adebayo 2001;Koyenikan 2008;Iwuchukwu and Igbokwe 2012;Akinbamowo 2013;Obiora and Emodi 2013;Hamisu et al 2017) and a report by FMARD (2012) suggests that several factors are responsible for the ineffectiveness and limited impact of agricultural extension policy in Nigeria. These factors include, for instance, absence of a legislated extension policy and policy inconsistency (Koyenikan 2008;FMARD 2012;Akinbamowo 2013;Obiora and Emodi 2013), funding complications and weak diversification (Iwuchukwu and Igbokwe 2012;Hamisu et al 2017), a low level of participation by the private sector in the delivery of extension services (Omotayo, Chikwendu, and Adebayo 2001;Iwuchukwu and Igbokwe 2012), weak synergy across government levels (FMARD 2012;Inegbedion et al 2019), weak capacity and technical know-how of extension personnel (Issa 2013;Suvedi, Ghimire, and Kaplowitz 2017) and inadequate manpower for the effective delivery of services (FMARD 2012; Obiora and Emodi 2013).…”
Section: Key Challenges Impeding Effective Implementation Of Agricultmentioning
confidence: 99%
“…The ADPs, which are still in existence, were launched and jointly funded by the World Bank and the federal and state governments. However, the effectiveness of the ADPs declined significantly soon after the World Bank withdrew its sponsorship (Iwuchukwu and Igbokwe 2012;Agber, Iortima, and Imbur 2013;Issa 2013;Hamisu et al 2017). Auta and Dafwang (2010) and Inegbedion et al (2018) suggested that the state ADPs in Nigeria were classified as having weak sources of funding, while Davis, Lion, and Arokoyo (2019) argued that there has been no improvement in terms of funding because there is little or no effort to diversify the sources of funding for agricultural extension services, at either the federal or state level.…”
Section: Funding Complications and Weak Diversificationmentioning
confidence: 99%
“…Consequently, its definition depends on the objective of the organisation providing the services. Agricultural extension as a service or a system which assists farmers, through educational procedures, in improving farming methods and techniques, increasing production efficiency and income and bettering their levels of living and uplifting the social and educational standard of rural life [2]. Furthermore, extension service is defined as extending of services or system which extends the educational advantages of an institution to persons unable to avail them in a normal manner [2].…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural extension as a service or a system which assists farmers, through educational procedures, in improving farming methods and techniques, increasing production efficiency and income and bettering their levels of living and uplifting the social and educational standard of rural life [2]. Furthermore, extension service is defined as extending of services or system which extends the educational advantages of an institution to persons unable to avail them in a normal manner [2]. The general role played by extension is to disseminate information, provide assistance and advice to farmers in order to increase their agricultural production and quality control procedures [3].…”
Section: Introductionmentioning
confidence: 99%